Religiosity, religious coping and distress among Muslim undergraduate students in UiTM Shah Alam / Mohd Hazreen Abdul Rashid - Abdul Rashid, Mohd Hazreen (2019)
Background: Researchers have shown that there is a relatively high prevalence of depression, anxiety and stress among university students compared to the general population due to their vulnerability towards the high demands of academic life and social changes. To minimize and mitigate the impact of the stressful events and environment, a person would use specific behavioural and cognitive adaptative methods called coping strategies or mechanism. Religiosity is a multi-dimensional sociological terms that describe an individual’s belief, religious attitudes and practices, religious identity, affiliation and participation in religious activities. Religious coping is the term used to describe coping mechanisms derived from a person’s religion or spirituality. Studies have shown that both negative and positive types of religious coping have significant association with outcomes like depression, anxiety and stress. Objective: The objective of the study is to determine the prevalence of depression, anxiety and stress among university students and examine the factors associated with them which include socio-demographic factors, the level of religiosity and the types of religious coping used. Methodology: This is a cross-sectional study conducted among four hundred and sixtyseven students in Universiti Teknologi Mara (UiTM) Shah Alam. The symptoms of depression, anxiety and stress were measured using the Malay version of Depression, Anxiety and Stress Scale (DASS-21). Religiosity and types of religious coping were each measured using the Hatta Islamic Religiosity Scale (HIRS96) and Brief Religious Coping Scale (Brief RCOPE) respectively. All questionnaires used had been translated into the Malay language version and validated. Results: 184 (39.7%) subjects showed the symptoms of depression with the severity ranging from mild to extremely severe. For the symptoms of stress and anxiety, the numbers of students were 270 (58.4%) and 157 (33.9%) respectively. The majority of subjects (89.6%) used positive religious coping while only 12.5% used negative religious coping. The religiosity score on HIRS 96 showed a mean of 60.58 (±SD 11.45). Using multiple logistic regression, significant associations were found between depression with age factor (p<0.05, OR 1.28) and the use of both positive (p<0.05, OR 0.33) and negative religious coping (p<0.05, OR 2.84). The symptoms of anxiety showed significant association with negative religious coping (p<0.05, OR 2.34), the female gender (p<0.05, OR 1.60) and also year of study (p<0.05, OR 1.55). The symptoms of stress were significantly associated with the female gender too (p<0.05, OR 2.25) and religiosity (p<0.05, OR 0.97). Conclusion: The present study demonstrated high prevalence of depression, anxiety and stress among the students of UiTM Shah Alam. Consistent significant associations were found between negative religious coping with both anxiety and depressive symptoms. Consistent with the earlier studies done among Muslim samples, the positive religious coping is not significantly associated with better psychological outcomes although only small effect was observed towards the depressive symptoms. Clinicians are recommended to exercise more empathy to allow a higher degree of openness when discussing negative reframing of religious concepts with a patient.